POTENSI PANAS BUMI SEBAGAI ENERGI ALTERNATIF PENGGANTI BAHAN BAKAR FOSIL UNTUK PEMBANGKIT TENAGA LISTRIK DI INDONESIA - Hilma Meilani; Dewi Wuryandani (Pusat Penelitian, Badan Keahlian DPR RI, 2010)
Geothermal energy is a renewable and environmentally friendly natural resource. Indonesia is estimated to hold approximately 40% of the world’s geothermal reserves, equivalent to some 28.000 MW of power, one of the biggest geothermal resources in the world. The electrification ratio of Indonesia in 2009 was around 65%, and the utilisation of geothermal energy for electricity in Indonesia is still very low, around 1.189 MW. The government of Indonesia has been trying to provide a better investment climate for geothermal development in Indonesia by issuing regulations and presidential decrees to support future developments. This paper, which is a secondary data based-descriptive analysis, describes the prospect of geothermal energy as an alternative energy to reduce power generation’s dependency on fossil fuel and the relevant government policies may be developed for geothermal energy development in Indonesia. Besides, this paper also emphasizes the role of geothermal energy to prevent climate changes and global warming as indicated by positive link between the use of geothermal energy and low greenhouse gases emission, and its role to decrease government subsidy for fuel oil based power plant.